Did Portraiture Exist as a Genre in Classical Antiquity? About One of the Problems in Art Theory - Trofimova, Anna A. (Actual Problems of Theory and History of Art, 2017)
The definition of ancient portraiture is a subject of controversy. It is well known that ancientportraiture was of fundamental importance for West-European art, and it was in Classical antiquity that basic forms of sculptural portraiture were created. It was then that artistic language appeared, and the tradition o finstalling statues in socially significant places was established, Despite that in the second half of the 20th — early 21st century art historians came to a paradoxical conclusion: Classical antiquity was a non-portraiture periodwith a collective-minded society missing an image of a personality. Similarity, individuality and type, the conceptof realism, mythological and historical ideas are the key categories in contemporary interpretation of portraiture.The author of the article considers these categories referring to the main stages in the history of portraitin antiquity, and revealing the deep specificity of the ancient portraiture. Its principal characteristic was being true to type — the exact similarity between an image and a person basically was of no importance — an image appeared as a combination of mythological and individual traits. The second crucial factor is replication of the original that determines methods of creating and perception: thus, unique is the archetype, not a single work of art. The author comes to the conclusion that contemporary categories treat a portrait within extra-artistic problems, and it is necessary to return to the very essence of the portrait genre. Portrait sculpture of Classical antiquity as a three-dimensional model of reality should be referred to as the embodiment of genuine traits of portrait image.
Keywords: portrait genre; antique portrait; sculptural portrait; art theory; art history; copying; replication